Promosi SDGs Poin 11 dan 15 melalui Program Kerja Gemar Menanam oleh Mahasiswa Kuliah Kerja Nyata (KKN) di Kelurahan Tuah madani - Ikhsan Faturrahman; Novita Syafitri; Nabila Fathia Hasan; Amanda Faiz Tharissa Lubis; Bimo Abdya Batara; Raysa Purnama Ramadhani; Karent Uda Samara; Muhammad Uwais; Muhammad Ihsan Rahmat; Kayyis Alfa Sabriy Izti; Geubri Habibie; Raafi'ul Haqqy Sukma (Unri Conference Series: Community Engagement, 2025)
The GEMAR MENANAM (Tuah Madani Planting Movement) program is a community service initiative conducted by Universitas Riau’s MBKM Community Service Program (KKN MBKM) to address the issue of limited green spaces in Tuah madani Sub-district, Pekanbaru. Rapid residential development has significantly reduced open land availability, resulting in environmental degradation. To respond to this problem, the program adopted a participatory approach by involving local communities and the sub-district government, combined with field observations to identify areas with potential for greening. The results of the program demonstrated that vacant land in RW 07 was successfully transformed into productive green areas through the cultivation of fruit-bearing and ornamental plants. These findings highlight that a community-based participatory method is effective in raising environmental awareness while supporting the implementation of the Sustainable Development Goals (SDGs), particularly Goal 11 (Sustainable Cities and Communities) and Goal 15 (Life on Land). In conclusion, GEMAR MENANAM not only contributes directly to local environmental management but also provides a replicable model of community empowerment that can be applied in other urban areas to promote sustainable development.